Structural conflict and democratic self-sabotage in Africa: a decolonial-conceptual statement - Dan Suleiman, Muhammad (Frontiers in Political Science, 2025)
This article is a conceptual intervention in the debate on the so-called democratic backsliding in Africa, and challenges the dominant narratives for overlooking more fundamental structural questions. Rather than mere erosion of democratic gains, I contend that recurring crises of democratization are manifestations of an enduring Structural Conflict (SC) in the political culture of African countries. SC refers to the dissonance between colonial political structures and indigenous popular agency. To capture this, I introduce two types of political agency—Dominant Majority Demo-Agency (DMD+), where citizens exercise genuine control, and Dominant Minority Demo-Agency (DMD−), where elites monopolize power—as novel tools for diagnosing Africa’s hollow democratic transitions. Building on Frantz Fanon’s analysis of coloniality, I theorize internalized structural inferiority as the mechanism through which many African states valorize external models and devalue indigenous ones. It is this internalization, I argue, that generates democratic self-sabotage: the embrace of alien structures that appear democratic while disabling majority agency and manifesting in coups, violent extremism, electoral disillusionment, and conflict. While recognizing Africa’s diversity, I propose Structural Blackening as a corrective: the deliberate reconstitution of political systems with indigenous agency, epistemologies, and aspirations. Structural Blackening offers a path toward authentic democratic emancipation rooted in epistemic and structural rebellion against coloniality.